2021
DOI: 10.36227/techrxiv.16844521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transfer Learning Strategies for Anomaly Detection in IoT Vibration Data

Abstract: <div>Abstract—An increasing number of industrial assets are equipped with IoT sensor platforms and the industry now expects data-driven maintenance strategies with minimal deployment costs. However, gathering labeled training data for supervised tasks such as anomaly detection is costly and often difficult to implement in operational environments. Therefore, this work aims to design and implement a solution that reduces the required amount of data for training anomaly classification models on time series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…While some traditional methods for fault detection require feature engineering (Kato, Yairi, & Hori, 2001;Su, Sun, Gao, Qiu, & Tian, 2019;J. Wang et al, 2020), recent work has shown that end-to-end autoencoders can outperform traditional approaches (Zong et al, 2018;Maleki, Maleki, & Jennings, 2021;Heistracher, Jalali, Suendermann, et al, 2021). Autoencoders are promising and have been for minimal-configuration fault detection (Heistracher, Jalali, Suendermann, et al, 2021;Hood et al, 2021), however this unsupervised methods lack the ability for fault classification or fault location.…”
Section: Related Workmentioning
confidence: 99%
“…While some traditional methods for fault detection require feature engineering (Kato, Yairi, & Hori, 2001;Su, Sun, Gao, Qiu, & Tian, 2019;J. Wang et al, 2020), recent work has shown that end-to-end autoencoders can outperform traditional approaches (Zong et al, 2018;Maleki, Maleki, & Jennings, 2021;Heistracher, Jalali, Suendermann, et al, 2021). Autoencoders are promising and have been for minimal-configuration fault detection (Heistracher, Jalali, Suendermann, et al, 2021;Hood et al, 2021), however this unsupervised methods lack the ability for fault classification or fault location.…”
Section: Related Workmentioning
confidence: 99%